2016
DOI: 10.3389/fpsyg.2016.00004
|View full text |Cite
|
Sign up to set email alerts
|

Processing Preference Toward Object-Extracted Relative Clauses in Mandarin Chinese by L1 and L2 Speakers: An Eye-Tracking Study

Abstract: The current study employed an eye-movement technique with an attempt to explore the reading patterns for the two types of Chinese relative clauses, subject-extracted relative clauses (SRCs) and object-extracted relative clauses (ORCs), by native speakers (L1), and Japanese learners (L2) of Chinese. The data were analyzed in terms of gaze duration, regression path duration, and regression rate on the two critical regions, head noun, and embedded verb. The results indicated that both the L1 and L2 participants s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Some of the previous self-paced reading studies also revealed similar results (Gibson and Wu, 2013 ); namely, ORCs were read faster on the head noun than SRCs. More recent eye-tracking studies also showed a similar pattern (Sung et al, 2015 , 2016 ), reporting shorter gaze durations and less regressions on the head noun for ORCs than for SRCs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Some of the previous self-paced reading studies also revealed similar results (Gibson and Wu, 2013 ); namely, ORCs were read faster on the head noun than SRCs. More recent eye-tracking studies also showed a similar pattern (Sung et al, 2015 , 2016 ), reporting shorter gaze durations and less regressions on the head noun for ORCs than for SRCs.…”
Section: Discussionsupporting
confidence: 52%
“…The evidence for ORC advantage in Chinese has been obtained from other methodologies, as well. In two eye-tracking studies (Sung et al, 2015 , 2016 ), less difficulty was consistently found in reading ORCs than SRCs by means of multiple eye-movements measures especially on the head noun. Neuropsychological results also indicated that ORCs were comprehended better than SRCs in aphasic patients of agrammatism and other types (Law, 2000 ; Law and Leung, 2000 ; Su et al, 2007 ).…”
Section: Introductionmentioning
confidence: 97%
“…Since then, there have been numerous attempts to either refute these claims or provide support for the ORC advantage. Previous studies supporting an SRC advantage have used eye-tracking [ 17 ] and self-paced reading [ 18 , 19 , 20 ], and studies supporting an ORC advantage have used eye-tracking [ 21 , 22 ], event-related potentials [ 23 , 24 ], the maze task [ 25 ], and self-paced reading [ 26 , 27 , 28 ]. The amount of support for each claim using a variety of methods makes this issue highly contested.…”
Section: Introductionmentioning
confidence: 99%
“…Although ultimate attainment is still debated, recent studies have focused on comparison of native speakers vs. non-native speakers that were familiar with the language for a long time prior to the study (Meulman et al, 2015; Díaz et al, 2016; Hanna et al, 2016; Johnson et al, 2016; Sung et al, 2016). However, few of them used a technique that allowed for source localization (Hanna et al, 2016).…”
Section: Discussionmentioning
confidence: 99%